2012
DOI: 10.1021/ja211347n
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Synthesis Inspired by Biomineralization: Control of Morphology, Crystal Phase, and Light-Use Efficiency in a Single Process

Abstract: Hydroxyapatite is mineralized along the long axis of collagen fiber during osteogenesis. Mimicking such biomineralization has great potential to control inorganic structures and is fast becoming an important next-generation inorganic synthesis method. Inorganic matter synthesized by biomineralization can have beautiful and functional structures that cannot be created artificially. In this study, we applied biomineralization to the synthesis of the only photocatalyst in practical use today, titanium dioxide (Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 35 publications
3
89
0
Order By: Relevance
“…To date, the synthesis of inorganic crystals with controlled morphology has been focused mainly on common inorganic biominerals, such as calcium carbonates [5,6] and calcium phosphates [7][8][9][10]; however, the number of target substances for biomimetic mineralization is currently being expanded beyond common inorganic biominerals [11][12][13]. Layered double hydroxides (LDHs) form one class of substances that are targeted for morphological control through a biomimetic approach [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the synthesis of inorganic crystals with controlled morphology has been focused mainly on common inorganic biominerals, such as calcium carbonates [5,6] and calcium phosphates [7][8][9][10]; however, the number of target substances for biomimetic mineralization is currently being expanded beyond common inorganic biominerals [11][12][13]. Layered double hydroxides (LDHs) form one class of substances that are targeted for morphological control through a biomimetic approach [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This observation has yielded a peptide design guideline for interfacing peptides with TiO 2 such that peptides exhibiting exposed lysine and/or arginine residues possess the mineralization property. It has also been reported that mineralization of metal oxides on self-assembled peptide surfaces can dictate the morphology of the inorganic material 21,31 . To that effect, the peptides discussed here, c16-AHL 3 K 3 -CO 2 H and c16-AHL 3 K 9 -CO 2 H, are excellent candidates for exploring TiO 2 mineralization.…”
Section: Resultsmentioning
confidence: 97%
“…The design has been shown to bind and organize a variety of metalloporphyrins on extensive length scales in the form of fibrillar structures 15 . The resulting structure produces a surface rich in lysine residues, which have been shown to induce TiO 2 mineralization by both unassembled and assembled peptide systems in good yield [16][17][18][19][20][21] . The final material is a peptide fibre that internally binds a metalloporphyrin and externally mineralizes TiO 2 .…”
mentioning
confidence: 99%
“…Currently, the most-applied synthetic strategy for the preparation of TiO 2 hollow structures relied on the use of sacrificial templates, including hard or soft template, and the desired hollow interiors are generated upon the removal of templates by calcinations or dissolution [14][15][16][17]. For example, Tang et al [18] prepared TiO 2 hollow structures using resorcinol-formaldehyde resin spheres as templates.…”
Section: Introductionmentioning
confidence: 99%